In vitro metabolism of obovatol and its effect on cytochrome P450 enzyme activities in human liver microsomes. (26th March 2013) - Joo, Jeongmin; Lee, Doohyun; Wu, Zhexue; Shin, Jung‐Hoon; Lee, Hye Suk; Kwon, Byoung‐Mog; Huh, Tae‐Lin; Kim, Yang‐Weon; Lee, Su‐Jun; Kim, Tae Wan; Lee, Taeho; Liu, Kwang‐Hyeon
ABSTRACT Obovatol, a major constituent of the leaves of Magnolia obovata Thunb, is known to inhibit nuclear factor‐κB activity and arachidonic acid‐induced platelet aggregation. This study was performed to identify the metabolites of obovatol in human liver microsomes. Human liver microsomes incubated with obovatol in the presence of NADPH and/or UDPGA resulted in the formation of six metabolites, M1–M6. M1 and M2 were identified as hydroxyobovatol, on the basis of liquid chromatography/tandem mass spectrometric (LC‐MS/MS) analysis. M1, M2 and obovatol were further metabolized to their glucuronide conjugates, obovatol‐glucuronide (M3), obovatol‐diglucuronide (M4) and hydroxyobovatol‐glucuronide (M5 and M6). The inhibitory potency of obovatol on eight major human P450s was also investigated in human liver microsomes. In these experiments, obovatol strongly inhibited CYP2C19‐mediated S‐mephenytoin hydroxylase activity with an IC50 value of 0.8 µm, which could have implications for drug–drug interactions. Copyright © 2013 John Wiley & Sons, Ltd.